The Application of the Combination of Number and Shape in the Process of Mathematics Learning - Jinyi Yan; Jingyao Zheng (International Journal of Engineering and Management Research, 2019)
The mathematical idea of ​​combining numbers and shapes is an indispensable part of mathematics learning process. It is widely used and has certain difficulties in the process of application. Therefore, in the process of learning, we should properly classify and summarize. In this regard, in this paper, the mathematical combination ideas are introduced and summarized in the aspects of equations and inequalities, analytic geometry and linear programming.